Warfarin and Aspirin Use for Stroke Prevention Among Patients With Atrial Fibrillation: The US National Health and Wellness Survey. (July 2015) - Goren, Amir; Liu, Xianchen; Gupta, Shaloo; Simon, Teresa A.; Phatak, Hemant
Abstract : Vitamin K antagonist (VKA) and aspirin (ASA) are recommended for stroke prevention in patients with atrial fibrillation (AF). This study examined VKA and ASA use and their clinical correlates, including CHADS2 stroke risk scores, among adult patients with AF in the general population. Participants included 1290 (1.72%) adults reporting diagnosis with AF (mean age, 64.9 years; 65% men) from the 2009 US National Health and Wellness Survey, an online, self-administered, nationwide, stratified random sample survey of 75, 000 adults. Antithrombotic use patterns, including VKA, ASA, VKA+ASA, and non-VKA/ASA, and their correlates were examined using logistic regressions. Respondents with AF were treated with VKA (26.6%), ASA (34.5%), VKA+ASA (15.4%), or neither (23.5%). Among those with CHADS2 ≥1, 19.3% did not report use of VKA or ASA. Among those with CHADS2 ≥2, 35.7% were treated only with ASA. Adjusting for covariates in logistic regressions, CHADS2 ≥1 was associated with VKA and/or ASA (vs. non-VKA/ASA) use ( P ⩽ 0.02), but CHADS2 score did not differentiate VKA versus ASA use ( P > 0.4). Comorbidities were associated with ASA versus VKA use ( P ⩽ 0.01). Older age, male gender, married status, and obesity were each associated with use of at least one of the treatments investigated (all P < 0.05). One-in-five AF patients with CHADS2 ≥1 were untreated and more than one-third with CHADS2 ≥2 treated with only ASA for stroke prevention. Our findings suggest that although patient characteristics including CHADS2 score were associated with either VKA or ASA use, CHADS2 score was unrelated to VKA versus ASA treatment.